Al-Hijrah wa-‘alaqatuha bi-istiratijiyah da’wah Rasul Allah salla Allah 'alayh wa-salam - Rashidah Bt Muhammad Nur (Kolej Universiti Islam Malaysia, 2014)
This research paper discussed on Hijrah ( migration) and its connection with the effective dakwah activities and performance conducted by the Rasulullah SAW. The study also includes the concept and terminology of the word " Hijrah" and the concept of Hijrah as stated in the Al-Quran and the Sunnah. The study looks into the factors that led to the migration of the Rasulullah from Makkah to Madinah. It also looks into the Dakwah strategies carried out during the Hijrah in the propagation of the new religion of Islam conducted by Rasulullah SAW. The Prophet managed to organize an Islamic society in Madinah. The prophet among others, built mosque, united the Muhajirin and the Amar tribes. He also managed to introduce the written charter that is known as the charter of Madinah. Finally, the study concludes that there are several positive facets of the Dakwah methods and approaches that were practiced by Rasulullah SAW, and among them, can be practiced by the Islamic Scholars and missionaries in Malaysia today.